PEMBINAAN PEMBENTUKAN MEDIA INTERAKTIF GURU DENGAN METODE TGT (TEAMS GAMES TOURNAMENT) BERBASIS WORDWALL DI MIN 4 PALANGKA RAYA - Surawan, Surawan; Husniah, Laila (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2024)
Interactive learning is key to improving student engagement and understanding in class. This community service aims to guide grade 1 teachers at MIN 4 Palang Raya in creating interactive media based on Word wall using the TGT (Teams Games Tournament) method. The TGT method was chosen because it is able to integrate game and competition elements that can motivate students to learn more actively and enjoyably. Community service activities include several stages, namely training in using the Word wall platform, designing interactive learning media, and implementation and evaluation in class. Teachers are given intensive assistance in utilizing various Word wall features to create various types of educational games that are relevant to the grade 1 curriculum. The results of this activity show an increase in teachers' abilities in creating and applying interactive media, as well as an increase in student participation and learning achievement in grade 1. Thus, coaching through the TGT method based on Word wall not only improves teachers' technical competence in creating interactive media, but also strengthens collaboration and innovation in the learning process in class. It is hoped that similar activities can continue to be carried out to support improving the quality of education in schools and other teachers.